Органы территориального общественного самоуправления в системе местного самоуправления - Мишина, Наталья Викторовна; Мішина, Наталія Вікторівна; Mishina, Natal'ja (My University, 2011)
The article is dedicated to the problem of reasonability of including the bodies of territorial social self-government to the municipal system. Author bases pros and contras of different approaches on the historic and foreign experience.
Мишина Н. В. Органы территориального общественного самоуправления в системе местного самоуправления / Н. В. Мишина // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 146-152.
Keywords: территориальное общественное самоуправление; местное самоуправление; общественные объединения; територіальне громадське самоврядування; місцеве самоврядування; громадські об'єднання; territorial self-government; local government; associations